2009
DOI: 10.3390/v1020210
|View full text |Cite
|
Sign up to set email alerts
|

Viroid Intercellular Trafficking: RNA Motifs, Cellular Factors and Broad Impacts

Abstract: Viroids are noncoding RNAs that infect plants. In order to establish systemic infection, these RNAs must traffic from an initially infected host cell into neighboring cells and ultimately throughout a whole plant. Recent studies have identified structural motifs in a viroid that are required for trafficking, enabling further studies on the mechanisms of their function. Some cellular proteins interact with viroids in vivo and may play a role in viroid trafficking, which can now be directly tested by using a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Viroids are noncoding pathogens that can infect a broad range of plants causing devastating diseases. How they can regulate the host gene expression through means other than encoding proteins for specific functions still remains unknown . In this sense, the proteomic analysis of viroid‐infected plants constitutes a new promising approach in order to better understand such a host–pathogen relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Viroids are noncoding pathogens that can infect a broad range of plants causing devastating diseases. How they can regulate the host gene expression through means other than encoding proteins for specific functions still remains unknown . In this sense, the proteomic analysis of viroid‐infected plants constitutes a new promising approach in order to better understand such a host–pathogen relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, structural, and cellular studies on loop 7 (U43/ C318) showed that it is required for PSTVd movement from the bundle sheath into the phloem in N. benthamiana (Zhong et al, 2007;Takeda and Ding, 2009). Structural analysis of this loop region suggested that it might be associated with water insertion, which would distort the local helix, creating a pocket for protein binding.…”
Section: Box 51 Replication Of Viroidsmentioning
confidence: 99%
“…In situ hybridization showed presence of PSTVd NB in all cell types, but restriction of PSTVd NT to the phloem and bundle sheath cells of a systemic leaf. (A) From Zhong et al (2008) and (B) from Takeda and Ding (2009) with permission of the publishers. Nucleotide swapping between the two strains showed that four of the 5 nt differences are responsible for the competency of PSTVd NB to move out of bundle sheath cells.…”
Section: Box 51 Replication Of Viroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic identification of such factors is currently not feasible because all known viroid hosts are not amenable to efficient mutagenesis screening. Biochemical identification of viroid‐interacting proteins, followed by functional studies using targeted gene knockout or knockdown strategies will likely remain a major approach in the perceivable future (Takeda and Ding 2009).…”
Section: Future Directions Of Researchmentioning
confidence: 99%